Relationship between Helicobacter Pylori infection and Gastro-esophageal Reflux Disease - Sami Ullah, Humaira; Ibrahim, Mohammed (Journal of Neonatal Surgery, 2025)
Background:According to research, eradication of Helicobacter Pylori (Hp) infection may be followed by development of Gastro-Esophageal Reflux Disease (GERD), there has been concern regarding the interactions between Hp and GERD. Aim: This study aims to investigate the relationship between Helicobacter Pylori (H. pylori), and oesophagitis (non-erosive or erosive) in patients with reflux symptoms. Material and method: A total of 50 patients, fulfilling the inclusion criteria, were enrolled after taking informed consent. Endoscopy (and/or non-invasive tests like stool antigen test SAT, Serology: Non-invasive) was performed in all patients. On endoscopy, focusing on severity of esophagitis, either non-erosive or erosive esophagitis. During endoscopy, tissue biopsies were obtained for histopathology, which were then forwarded to the pathology lab for H. pylori detection. Results: Out of the total of 50 individuals, males were 21(42%) and females were 29(58%). The mean age of the study population was 36.01+7.41 (ranged 15-65) years. H. Pylori was reported in 15(30%) cases, signifying that 35(70%) of GERD cases were H. Pylori negative. Out of a total of 50 participants, the endoscopic findings revealed Non Erosive Reflux Disease (NERD) in 42(84%) cases and Erosive Esophagitis in 8(16%) cases. H. Pylori was positive in 3(20%) of erosive esophagitis patients and in 12(80 %) of NERD patients, (P< 0.3). Conclusion: The present study concluded that H. Pylori was present in 30% cases of GERD. Out of which, non-erosive reflux disease was associated with a greater frequency of helicobacter infection. Overall, the patients having GERD are more probable to have non-erosive reflux disease versus erosive esophagitis on endoscopy.